\newcommand{\w}{\mathbf{w}} \newcommand{\sqrterr}{\sum_{n=1}^N(y(x_n, \w) - t_n)} \newcommand{\half}{\frac{1}{2}} \newcommand{\dydw}{\frac{\partial y(x_n, \w)}{\partial \w}} \newcommand{\dydwi}{\frac{\partial y(x_n, \w)}{\partial w_i}} \newcommand{\Aij}{\sum_{n=1}^N (x_n)^{i+j}} \newcommand{\Ti}{\sum_{n=1}^N(x_n)^i t_n}
\begin{align*} &\sum_{j=0}^M A_{ij}w_j &=& T_i \ &\sum_{j=0}^M \sum_{n=1}^N (x_n)^{i+j} w_j &=& \sum_{n=1}^N(x_n)^i t_n \ &\sum_{n=1}^N \sum_{j=0}^M (x_n)^{i+j} w_j - \sum_{n=1}^N(x_n)^i t_n &=& 0 \ &\sum_{n=1}^N (\sum_{j=0}^M (x_n)^{i+j} w_j - (x_n)^i t_n) &=& 0 \ &\sum_{n=1}^N ( (x_n)^i \sum_{j=0}^M (x_n)^j w_j - (x_n)^i t_n) &=& 0 \ &\sum_{n=1}^N (x_n)^i (\sum_{j=0}^M (x_n)^j w_j - t_n) &=& 0 \ &\sum_{n=1}^N (x_n)^i (y(x_n, \mathbf{w}) - t_n) &=& 0 \ \end{align*}
Take derivative of
In order to minimize
Therefore, the statement is true.
Take derivative of
In order to minimize
\begin{align*} p(apple) &= p(apple|r)p(r) + p(apple|b)p(b) + p(apple|g)p(g) \ &= 0.3 \cdot 0.2 + 0.5 \cdot 0.2 + 0.3 \cdot 0.6 \ &= 0.06 + 0.1 + 0.18 \ &= 0.34 \end{align*}
\begin{align*} p(g|orange) &= \frac{p(g, orange)}{p(orange)} \ &= \frac{p(orange|g)p(g)}{p(orange|r)p(r) + p(orange|b)p(b) + p(orange|g)p(g)} \ &= \frac{0.3 \cdot 0.6}{0.4 \cdot 0.2 + 0.5 \cdot 0.2 + 0.3 \cdot 0.6} \ &= \frac{0.18}{0.08 + 0.1 + 0.18} \ &= \frac{0.18}{0.36} \ &= 0.5 \end{align*}
\begin{align*} var[f] &= E[(f(x) - E[f(x)])^2] \ &= E[f(x)^2 - 2f(x)E[f(x)] + E^2[f(x)]] \ &= E[f(x)^2] - E^2(f(x)) \end{align*}
If
Therefore, \begin{align*} cov(x, y) &= E_{x,y}[(x-E[x])(y-E[y])] \ &= E_{x,y}[xy] - E[x]E[y] \ &= 0 \end{align*}